All international politics is local : the diffusion of conflict, integration, and democratization - Gleditsch, Kristian Skrede, 1971- (The University of Michigan Press, 2002)
Looks at disparate zones in the international system to see how conflict, integration, and democracy have clustered over time and space. Kristian Skrede Gleditsch argues that the most interesting aspects of international politics are regional rather than fully global or exclusively national.